Circular RNA circCPA4 promotes tumorigenesis by regulating miR‐214‐3p/TGIF2 in lung cancer - Wenhu Tao; Cheng Cao; Gaofei Ren; Decun Zhou (Thoracic Cancer, 2021)
Abstract Background Lung cancer is the most prevalent malignancy in adults. Circular RNA (circRNA) circCPA4 (hsa_circ_0082374) is highly expressed in non‐small cell lung cancer (NSCLC). The purpose of this study was to explore the role and mechanism of circCPA4 in lung cancer. Methods CircCPA4, linear CPA4, TGF‐β‐induced factor homeobox 2 (TGIF2), and microRNA‐214‐3p (miR‐214‐3p) levels were measured by real‐time quantitative polymerase chain reaction (RT‐qPCR). The protein levels of TGIF2, Beclin1, and p62 were assessed by western blot assay. Colony numbers, migration, invasion, apoptosis, and cell cycle progression were examined by colony formation, wound‐healing, transwell, and flow cytometry assays, respectively. The binding relationship between miR‐214‐3p and circCPA4 or TGIF2 was predicted by StarBase or TargetScan and then verified by a dual‐luciferase reporter, RNA immunoprecipitation (RIP), and RNA pulldown assays. The biological role of circCPA4 on lung tumor growth was assessed by a xenograft tumor model in vivo, and TGIF2 and ki‐67 expression was assessed by immunohistochemistry. Results We determined that CircCPA4 and TGIF2 were increased, and miR‐214‐3p was decreased in lung cancer tissues and cells. Functionally, circCPA4 knockdown could suppress colony formation, migration, invasion, cell cycle progression, and expedite apoptosis of lung cancer cells in vitro. Mechanically, circCPA4 could regulate TGIF2 expression by sponging miR‐214‐3p. In addition, circCPA4 deficiency inhibited the tumor growth in lung cancer in the mouse model. Conclusions CircCPA4 could act as a sponge of miR‐214‐3p to upregulate TGIF2 expression, thereby promoting the progression of lung cancer cells. These findings suggested underlying therapeutic targets for the treatment of lung cancer.